2020
DOI: 10.1136/bjsports-2019-100755
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-week window for recurrent muscle strains in football: a prospective cohort of 3600 muscle strains over 23 years in professional Australian rules football

Abstract: ObjectivesTo determine the rates of muscle strain injury recurrence over time after return to play in Australian football and to quantify risk factors.MethodsWe analysed Australian Football League player data from 1992 to 2014 for rates of the four major muscle strain injury types (hamstring, quadriceps, calf and groin) diagnosed by team health professionals. Covariates for analysis were: recent history (≤8 weeks) of each of the four muscle strains; non-recent history (>8 weeks) of each; history of hip, kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…One of the most frequent sports injuries and the third most common in a survey of injuries occurring during the Olympic Games in Rio de Janeiro is muscle strain, after sprain/ligament rupture and contusion/hematoma/bruise (Soligard et al, 2017). Regarding incidence of muscle strain, the hamstrings, quadriceps, and triceps muscles are the most frequently involved (Garrett, 1996;Orchard et al, 2020). In a study, which used MRI, the rectus femoris (RF) muscle was the reported preferred muscle strain site of the quadriceps muscle (Cross et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequent sports injuries and the third most common in a survey of injuries occurring during the Olympic Games in Rio de Janeiro is muscle strain, after sprain/ligament rupture and contusion/hematoma/bruise (Soligard et al, 2017). Regarding incidence of muscle strain, the hamstrings, quadriceps, and triceps muscles are the most frequently involved (Garrett, 1996;Orchard et al, 2020). In a study, which used MRI, the rectus femoris (RF) muscle was the reported preferred muscle strain site of the quadriceps muscle (Cross et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data about the athlete’s age and injury history (early recurrence: previous ankle injury; overall: previous CMSI) were associated with a greater risk of recurrent CMSI. Recent studies similarly found older age and history of CMSI to be risk factors for CMSI, 19,39 and clinical data provide better information than MRI findings about the risk of recurrent hamstring muscle strain injuries. 12 A previous muscle strain injury can result in persistent strength deficits, 6,17,38 atrophy, 6,25,38,49 and noncontractile tissue infiltration, 20,38 as well as neurophysiological changes (eg, inhibition).…”
Section: Discussionmentioning
confidence: 94%
“…Soleus intramuscular aponeurosis injuries with AD had a slower functional progression when compared with injuries at the same location with no AD (Table 2). Patients with myofascial injuries had the shortest time on average to achieve pain-free [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. There was no difference in time to RTP between CMSI with no AD versus mild AD (r = 0.22; P = .06), or mild AD versus severe AD (r = 0.15; P = .30).…”
Section: Return To Playmentioning
confidence: 99%
“…Muscle strain is a frequent sports injury and occurs most often in hamstrings, quadriceps [especially the rectus femoris (RF)], and gastrocnemius ( Schuermans et al, 2016 ; Soligard et al, 2017 ; Orchard et al, 2020 ). To prevent muscle strain, it is important to decrease the muscle-tendon unit stiffness ( Watsford et al, 2010 ; Pickering Rodriguez et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%